Health-care providers' views on pursuing reproductive benefit through newborn screening: the case of sickle cell disorders - Bombard, Yvonne (Nature Publishing Group, 2012)
Newborn screening (NBS) programs aim to identify affected infants before the onset of treatable disorders. Historically, benefits to the family and society were considered secondary to this clinical benefit; yet, recent discourse defending expanded NBS has argued that screening can in part be justified by secondary benefits, such as learning reproductive risk information to support family planning (‘reproductive benefit'). Despite increased attention to these secondary benefits of NBS, stakeholders' values remain unknown. We report a mixed methods study that included an examination of providers' views toward the pursuit of reproductive risk information through NBS, using sickle cell disorder carrier status as an example. We surveyed a stratified random sample of 1615 providers in Ontario, and interviewed 42 providers across 7 disciplines. A majority endorsed the identification of reproductive risks as a goal of NBS (74–77%). Providers' dominant rationale was that knowledge of carrier status is an important and inherent benefit of NBS as it allows people to make reproductive choices, which is consistent with the goals of disease prevention. However, some challenged its appropriateness, questioning its logic, timing and impact on disease prevention. Others were sensitive to intruding on individuals' choices or children's independent rights. While the dominant view is consistent with discourse defending expanded NBS, it deviates from the traditional screening principles that underpin most public health interventions. Broader discussion of the balance between benefits to screened individuals and those to families and societies, in the context of public health programs, is needed.